Feminist translation equivalence and norms: gender and female alienation in Chinese translation of Chinese American women's literature - Tang, Beibei (2018)
Drawing on three Chinese translations each of Amy Tan's The Joy Luck Club (1989) and The Kitchen God's Wife (1991), this project examines, from a feminist perspective, gender issues in Chinese translations of Chinese American women's literature, with special attention paid to the translators' gender consciousness and ideologies as reflected in their translations of ‘female alienation’. Existing studies on Chinese American women's literature, in both America and mainland China, mainly address identity politics, culture, Orientalism, and feminism, and fail to consider the role of translation. This project, however, analyses both the feminist consciousness and the issues which are reflected in these two novels and in their Chinese translations. This project innovatively applies the feminist concept of ‘female alienation’ to literary translation studies. The concept of ‘female alienation’, which originates from Karl Marx's theory of labour alienation, is developed by Alison Jaggar through feminist discussions of women's oppression and subordinate status. Women in a patriarchal society are alienated by men's power and separated from their self and nature; this leads to their loss of subjectivity and independence. Jaggar believes that women are alienated in all aspects of their lives, particularly in their sexuality, motherhood, and intellectual capacities, and this project discusses the influence of race and self-Orientalization on that alienation. Indeed, it enriches Jaggar's concept of female alienation by adding sisterhood alienation. A new classification is then proposed to study different patterns of alienation and women's psychological experiences with it, both active and passive, as reflected in Tan's works and the Chinese translations of those works. In terms of translation studies, this project combines translation equivalence and norms theories with feminist translation theory; it proposes a set of feminist translation norms and a concept of feminist translation equivalence to study feminist translation in the Chinese context. Feminist translation norms include feminist preliminary, expectancy, operational, accountability, communication, and relation norms. It is the feminist preliminary and expectancy norms that are used to analyse the translators' motives, intentions, and expectations of their translation. The feminist operational norm is used to analyse the translation strategies adopted by the translators. The feminist accountability norm refers to feminist translation ethics of fidelity; that is, the translation must be faithful to the writer's, or the translator's, own feminist consciousness, thoughts, and intentions. The feminist communication norm means that translations convey the writer's, or translator's, own feminist thoughts to the maximum possible extent. The feminist relation norm means that the relationship between the translation and the source text is the feminist translation equivalence, which means that the feminist thoughts reflected by the words or expressions in the source text, or by the translators' own feminist thoughts, are “faithfully” represented in the translation, even if the translator does not use the precisely equivalent words or expressions to achieve linguistic equivalence. Comparing the Chinese translations in order to study the translators' translation behaviours and the effects of their translations, this project explores how the feminist consciousness and thoughts on female alienation of the source text are represented in the Chinese translations, and in what way the translations achieve (feminist) translation equivalence. Summarising the regularities of the translation behaviour of the translator subgroups, and the (feminist) translation equivalence the translations achieve, this project provides evidence that the feminist translation ethics of fidelity do not necessarily contradict the traditional translation ethics of fidelity which focuses on linguistic equivalence. Meanwhile, it also verifies that so-called “feminist translation strategies” actually refer to all translation strategies which help the translations achieve feminist translation equivalence. This corrects the research misconception concerning feminist translation strategies in mainland China. Finally, by examining the translators' motives and expectations, reflected in their paratexts as well as in the translations, this project summarises feminist translation norms in the Chinese context, and defines the role of gender in translating female alienation in the texts in question.